The use of fondaparinux for the treatment of venous thromboembolism in a patient with heparin-induced thombocytopenia and thrombosis caused by heparin flushes - Alex C Spyropoulos; Sharyl Magnuson; Sei Keng Koh (Dove Medical Press, 2008)
Alex C Spyropoulos1, Sharyl Magnuson1, Sei Keng Koh21Clinical Thrombosis Center, Lovelace Medical Center, Albuquerque, NM, USA; 2Department of Pharmacy, Singapore General Hospital, SingaporeAbstract: Heparin-induced thrombocytopenia (HIT) is an immunologic drug reaction characterized by paradoxical association with venous and arterial thrombosis. The syndrome is caused by IgG antibodies that are reactive against complexes of platelet factor 4 and heparin. Fondparinux does not bind to platelet factor 4, is structurally too short to induce an antibody response, and could in theory be a useful agent to treat HIT. A 69-year-old white female presented with a lower extremity extensive iliofemoral deep vein thrombosis after a right total knee arthroplasty and was subsequently found to have a pulmonary embolism. The patient was noted to have heparin flushes during her operation. Her platelet drop decreased >50% from baseline during initiation of antithrombotic therapy. She was started on subcutaneous fondaparinux 7.5 mg once daily injection. Her serotonin release assay and enzyme-linked immunosorbent assay for heparin antibodies were positive for HIT. Her platelet count nadir was 60 × 103/mm3 on day 5 and the platelet count rebounded after 8 days of fondaparinux therapy. No recurrent thrombotic or bleeding events were noted throughout her therapy. Anecdotal reports have shown that fondaparinux can be a useful agent to treat HIT with or without thrombosis.Keywords: fondaparinux, heparin-induced thrombocytopenia with thrombosis (HITT)